Fear of Punishment in Another World: a Follow-Up Examination of the Religious Beliefs About HIV/AIDS—A Decade of Progress? - Parsons, Sharon (Journal of religion and health, 2022)
This study compared 2000 and 2010 data on the religious beliefs about HIV/AIDS among those with HIV in a Deep South state. The percentage agreeing that HIV/AIDS is a punishment from God had not decreased in that decade. The literature on interventions to reduce religious stigma and increase church involvement in HIV/AIDS prevention was presented. The study concluded with a set of recommendations for future research.